PANDEMIC INFLUENZA A (H1N1) 2009 PRESENTING AS A MILD DISEASE IN CHILDREN IN A CROATIAN CLINICAL CENTRE - Grgić, Svjetlana (Acta Clin Croat, 2019)
Pandemic influenza A virus (H1N1) 2009 causes a disease that is epidemiologically and clinically not significantly different from seasonal influenza, but there are differences. The aim of the study was to display and compare epidemiological and clinical characteristics of pandemic influenza in children. At Dr. Fran Mihaljević University Hospital for Infectious Diseases in Zagreb, in the first two seasons, the incidence of pandemic influenza virus A (H1N1) in particular was exhaustively analyzed only in patients with laboratory-confirmed pandemic influenza A virus (H1N1) 2009. In hospitalized children with documented influenza pandemic, moderate form of the disease predominated, which ultimately meant shorter hospital stay and fewer complications. Otitis media was the rarest complication in children in both seasons. In conclusion, children younger than 5 years, especially boys, were vulnerable groups for pandemic influenza, presenting as a mild disease with low mortality and few complications. Most of the affected children with influenza did not have important risk factors such as asthma and obesity, highlighted by other authors as significant risk factors.